The Influence Of Service Quality And Price On Customer Satisfaction - Saputra, Aditya Dwi Ramdhani; Maftuchach, Viniyati (Journal of Economics and Business (JECOMBI), 2025)
Consumers seek affordable prices that meet their needs while leveraging new opportunities to ensure the service quality provided satisfies prospective customers. The purpose of this study is to examine the influence of service quality and price on customer satisfaction. The research population consists of customers at the JNE Sales Counter of PT Forty Resource, with a sample size of 100 respondents. The data analysis method employed is multiple regression using SmartPLS 4, utilizing Structural Equation Modelling (SEM). The study results indicate that service quality has a positive but not significant effect on customer satisfaction, while price has a positive and significant effect on customer satisfaction. The implications of this study suggest that better service quality and competitive pricing can enhance customer satisfaction, particularly at the Sales Counter of PT Forty Resource. The limitations of this study include a sample size of only 100 respondents and reliance solely on data analysis results. Future research is encouraged to further explore service quality, price, and customer satisfaction using different research methods, a broader sample, and alternative research instruments. The use of SmartPLS 4 distinguishes this study from previous research.